Question
upstudy study bank question image url

\( \begin{array}{l}2 y=x+3 \\ 5 y=x-7 \\ \text { What is the solution set of the given system? } \\ \{(-29 / 3,-10 / 3)\} \\ \{(1 / 3,4 / 3)\} \\ {[(-1 / 3,-4 / 3)\}} \\ {[(29 / 3,10 / 3)\}}\end{array} \)

Ask by Peterson Huff. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is \( x = -\frac{29}{3} \) and \( y = -\frac{10}{3} \).

Solution

Solve the system of equations \( 2y=x+3;5y=x-7 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}2y=x+3\\5y=x-7\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2y-3\\5y=x-7\end{array}\right.\) - step2: Substitute the value of \(x:\) \(5y=2y-3-7\) - step3: Simplify: \(5y=2y-10\) - step4: Move the variable to the left side: \(5y-2y=-10\) - step5: Subtract the terms: \(3y=-10\) - step6: Divide both sides: \(\frac{3y}{3}=\frac{-10}{3}\) - step7: Divide the numbers: \(y=-\frac{10}{3}\) - step8: Substitute the value of \(y:\) \(x=2\left(-\frac{10}{3}\right)-3\) - step9: Calculate: \(x=-\frac{29}{3}\) - step10: Calculate: \(\left\{ \begin{array}{l}x=-\frac{29}{3}\\y=-\frac{10}{3}\end{array}\right.\) - step11: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{29}{3}\\y=-\frac{10}{3}\end{array}\right.\) - step12: Rewrite: \(\left(x,y\right) = \left(-\frac{29}{3},-\frac{10}{3}\right)\) The solution set of the given system of equations is \( \{(x,y) = (-\frac{29}{3},-\frac{10}{3})\} \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the system of equations, we need to express both equations in a form that's easier to work with. Start by rewriting the equations: 1. From the first equation \( 2y = x + 3 \), we can express \( y \) as \( y = \frac{x + 3}{2} \). 2. From the second equation \( 5y = x - 7 \), we can express \( y \) as \( y = \frac{x - 7}{5} \). Now, we can set these two expressions for \( y \) equal to each other: \[ \frac{x + 3}{2} = \frac{x - 7}{5} \] To eliminate the fractions, cross-multiply: \[ 5(x + 3) = 2(x - 7) \] Expanding both sides: \[ 5x + 15 = 2x - 14 \] Now, isolate \( x \): \[ 5x - 2x = -14 - 15 \\ 3x = -29 \\ x = -\frac{29}{3} \] Now that we have \( x \), we can substitute it back into one of the original equations to solve for \( y \). We can use the first equation: \[ 2y = -\frac{29}{3} + 3 \\ 2y = -\frac{29}{3} + \frac{9}{3} \\ 2y = -\frac{20}{3} \\ y = -\frac{10}{3} \] Thus, the solution set of the given system is: \[ \left\{ \left(-\frac{29}{3}, -\frac{10}{3}\right) \right\} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy